2015
DOI: 10.1175/jas-d-14-0265.1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Warm Rain Formation Process in Global Models with Satellite Observations

Abstract: This study examines the warm rain formation process over the global ocean in global climate models. Methodologies developed to analyze CloudSat and Moderate Resolution Imaging Spectroradiometer (MODIS) satellite observations are employed to investigate the cloud-to-precipitation process of warm clouds and are applied to the model results to examine how the models represent the process for warm stratiform clouds. Despite a limitation of the present study that compares the statistics for stratiform clouds in cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 84 publications
(110 citation statements)
references
References 42 publications
2
108
0
Order By: Relevance
“…Current microphysical frameworks without such macrophysical aspects bring highly sensitive aerosol-cloud interactions, although they vary to some extent depending on the autoconversion scheme (Gettelman, 2015;Suzuki et al, 2015;Michibata and Takemura, 2015). Ghan et al (2016) also reported a wide diversity in the LWP response to N c among various GCMs, and concluded that their inconsistency could mainly be attributed to their different representations of the autoconversion process.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current microphysical frameworks without such macrophysical aspects bring highly sensitive aerosol-cloud interactions, although they vary to some extent depending on the autoconversion scheme (Gettelman, 2015;Suzuki et al, 2015;Michibata and Takemura, 2015). Ghan et al (2016) also reported a wide diversity in the LWP response to N c among various GCMs, and concluded that their inconsistency could mainly be attributed to their different representations of the autoconversion process.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…1b, MIROC overestimates S conv , particularly in the lower LWP range. This means that the model generates precipitation at a higher frequency, even at low LWPs, compared to observations, which is mainly because the autoconversion in the model is too rapid (Michibata and Takemura, 2015;Suzuki et al, 2015), as described above. Consequently, the PDF of the LWP is biased toward lower values because cloud water is depleted quickly by the rapid surface precipitation.…”
Section: Precipitation Microphysicsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the general circulation models (GCMs) underestimated (overestimated) the cloud fraction (the radiative effect) in tropical low-level clouds (Nam et al, 2012) -so-called "too few, too bright" problem. Moreover, Suzuki et al (2015) reported that the warm cloud auto-conversion process in the GCMs was too rapid compared to that derived from satellite observation. It is necessary to understand the vertical structure of clouds to reduce the cloud bias in the GCMs.…”
Section: Introductionmentioning
confidence: 98%
“…Here we employ the Super-122 parameterized Community Atmosphere Model Version 5 (SPCAM5, Wang et al, 2015) to 123 provide the sub-grid cloud and precipitation hydrometeor fields for a comparison study of the 124 simulated radar reflectivity and warm rain frequencies by COSP. Fundamentally different from 125 the convectional cloud parameterization schemes in GCMs, SPCAM5 consists of a two-126 dimensional cloud-resolving model (CRM) embedded into each grid of a conventional CAM5 127 Wang et al, 2015). The sub-grid cloud dynamical and 128 microphysical processes are explicitly resolved at a 4-km resolution in SPCAM5.…”
mentioning
confidence: 99%